INFLUENCE OF TEMPERATURE ON THE HYDRO-MECHANICAL BEHAVIOUR OF A COMPACTED BENTONITE - Villar M.V.; Lloret A. (My University, 2004)
This paper reports the results on the influence of temperature (between 20 and 80 °C) on some hydro-mechanical properties of a compacted bentonite. The water retention capacity at higher temperature, both in confined and unconfined conditions, is lower, especially when suction is low. At high temperatures, the swelling capacity of clay decreases, although the influence of temperature is less evident when the applied stress is high. Furthermore, a decrease in swelling pressure as a function of temperature was observed. On the other hand, the measured increase in permeability with temperature is lower than expected on the basis of thermal change in water kinematic viscosity. The transfer induced by temperature between intra-aggregate adsorbed water and inter-aggregate free water may explain most of the features observed, taking into account that the physical characteristics (density, viscosity) of water in each one of these two states are different.
Keywords: Bentonite; Temperature; Permeability; Swelling; Water retention; Adsorbed water